INTEREST ANALYSIS OF COMPUTER ENGINEERING STUDENTS OF UNIVERSITAS WIRALODRA IN THE USE OF ELECTRONIC WALLETS - Wiji Prayitno, Seno; Hidayat, Taufik (Universitas Perwira Purbalingga, 2022)
Now technology is developing very rapidly. One of the fields that follow technological developments is in the financial sector. Financial technology (fintech) is an update in the financial sector that is centered on today's technology. One of the fintechs currently in development is a digital wallet (e-wallet). E-wallet is an application that stores nominal e-money and transactions can be carried out via mobile media by connecting the network to the internet. E-money is an electronic payment medium by first handing over a certain amount of money to the publisher, either directly or through the publisher's agents. For payment transactions by reducing the value of money on the e-money media. The study was conducted to analyze the interest of Computer Engineering students at Wiralodra University in using digital wallets as a modern technology. By distributing questionnaires to Computer Engineering students at Wiralodra University. The results of the media questionnaire were processed using multiple linear regression calculations. The results obtained from this study are students' interest in e-wallet with perceptions of convenience, efficiency and security.